Impact of the COVID-19 pandemic on acute mental health admissions in Croatia - Karolina Kalanj; Karolina Kalanj; Marko Ćurković; Marko Ćurković; Mirta Peček; Stjepan Orešković; Ante Orbanić; Rick Marshall (Frontiers in Public Health, 2023)
BackgroundThe pandemic of COVID-19 had a profound impact on our community and healthcare system. This study aims to assess the impact of COVID-19 on psychiatric care in Croatia by comparing the number of acute psychiatric cases before coronavirus disease (2017–2019) and during the pandemic (2020–2022).Materials and methodsThe paper is a retrospective, comparative analyzes of the hospital admission rate in Diagnosis Related Group (DRG) classes related to mental diseases, and organic mental disorders caused by alcohol and drug use. This study used DRG data from all acute hospitals in Croatia accredited to provide mental health care services and relevant publicly available data from the Croatian Institute of Public Health (CIPH) and the Croatian Health Insurance Fund (CHIF). All hospital admissions for acute psychiatric patients in Croatia were tracked during both periods under study.ResultsDuring the pandemic, the average number of all such cases decreased by 28% in secondary and tertiary hospitals, and by 11% in specialist psychiatric hospitals. It was also found that during COVID-19, there was a decrease in case numbers in DRG classes related to major affective disorders and anxiety, alcohol, and drug intoxication (31, 48, 34 and 45%, respectively). However, the same period saw an increase in hospital activity for eating disorders and for involuntary admissions related to schizophrenia and paranoia (30, 34 and 39% respectively). There were no changes in the admission rate for cases related to opioid use.ConclusionThe COVID-19 pandemic resulted in both a steep decrease in the overall number of psychiatric cases inpatient treatment at mental health facilities and their DRG casemix. Increasing our understanding of how pandemics and isolation affect demand for psychiatric care will help us better plan for future crises and provide more targeted care to this vulnerable group.